Upaya Meningkatkan Kemampuan Membaca Pemahaman Mahasiswa Melalui Metode PQ4R Pada Mata Kuliah Bahasa Jepang Prodi Administrasi Perkantoran D-3 Universitas Pamulang - Wulandari, Afrianti; Nurhayati, Nurhayati (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
The research entitled "Efforts to Improve Students' Reading Comprehension Ability Through the PQ4R Method in the Japanese Subject at Office Administration Diploma, Pamulang University." chosen by the author because it comes from the idea that there are still many students who are not fluent and do not understand the reading text, as a result most students are less active in reading. Lots of mistakes in pronouncing and understanding the text. Because of this problem, to help students easily remember the material they read from reading texts, learning methods are needed, one of which is the PQ4R method (Preview, Question, Read, Reflect, Recite and Review). The purpose of this study was to find out the efforts to improve students' reading comprehension skills through the PQ4R Method in the Japanese course at Office Administration Diploma, Pamulang University. The subjects of this study were students in the first semester of regular C class 661 Office Administration Diploma at Pamulang University with a total of 15 students. The method used in this study is the mix method. Quantitative analysis which consists of four steps: planning, action, observation, and reflection with the percentage increase, while qualitative analysis is carried out by analyzing data from the results of records fieldwork, tests, and documentation during research.